2009
DOI: 10.1021/jf901391a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Flavan-3-ol Profile and Antioxidant Capacity of Roasted Peanut, Hazelnut, and Almond Skins

Abstract: In the present study, the flavan-3-ol composition and antioxidant capacity of roasted skins obtained from the industrial processing of three commonly consumed tree nuts (i.e., peanuts, hazelnuts, and almonds), as well as fractions containing low and high molecular weight (LMW and HMW) flavan-3-ols, were studied with the aim of assessing their potential as a source of flavonoids. Roasted peanut and hazelnut skins presented similar total phenolic contents, much higher than that of almond skins, but their flavan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 47 publications
7
120
2
3
Order By: Relevance
“…The profiles observed in this study are similar to those previously reported [22,28]. Previous studies have confirmed that the procyanidin oligomers in peanut skins contain both B-linkages as well as the less common A-type linkages [28][29][30]. Overall, the profiles produced by the two solvent systems were similar; however, it is visually evident that acetone/water was a more effective extraction solvent for procyandins than ethanol/water as indicated by the larger peak areas.…”
Section: Procyanidin Contentsupporting
confidence: 87%
See 1 more Smart Citation
“…The profiles observed in this study are similar to those previously reported [22,28]. Previous studies have confirmed that the procyanidin oligomers in peanut skins contain both B-linkages as well as the less common A-type linkages [28][29][30]. Overall, the profiles produced by the two solvent systems were similar; however, it is visually evident that acetone/water was a more effective extraction solvent for procyandins than ethanol/water as indicated by the larger peak areas.…”
Section: Procyanidin Contentsupporting
confidence: 87%
“…Peanut skins have been reported to contain a variety of bioactive compounds with phenolic moieties, including catechins, A-type and B-type procyanidin dimers, trimers, and tetramers [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Extraction of these compounds has been studied with various extraction solvents.…”
Section: Total Phenolics and Antioxidant Activitymentioning
confidence: 99%
“…Polyphenols have been further characterised in hazelnut skins. Monagas et al (15) reported the catechin content and Del Rio et al (38) reported monomeric and oligomeric flavan-3-ols, flavonols, dihydrochalcones and phenolic acids in hazelnut skins. Although these studies did not report polyphenol content in terms of whole hazelnuts, monomeric and oligomeric (5) 2052 (28,80,86,92) 2713·49 (10 -12,18,28) 493·90 (1) 233·52 (70,169,170,175) ND Pine nuts 206 26 (5) ND 0·03 (11,12) 1 (11,13,18,43) § 190·75 (70,169,170,175,189,190) ND Pistachios 703 22 832 (5,50,87) 1·27 (191) 136·45 (10 -12,18,40,42,43,191) 252·71 (1) 189·43 (70,88,169 -171,175,192) 803·22 (40,43,48,49) Walnuts 1602 21 (5) 39·11 (44,51,60,193,194) 0·54 (11,…”
Section: Total Phenols and Flavonoidsmentioning
confidence: 99%
“…Contini ve ark. [23] [24]. Taş ve Gökmen [25] toplam antioksidan miktarının fındık iç kabuğunda fındığa göre 100 kat, α-tokoferolün iki kat daha fazla olduğunu fındık içi kabuğunun çekirdekle karşılaştırıldığında biyoaktif bileşenlerce zengin bir kaynak olabileceğini belirtmişlerdir.…”
Section: Yağlı Tohum Kabuklarının Fenolik Bileşenleri Ve Antioksidan unclassified